Analisis Hubungan Kepemimpinan Dan Tuntutan Tugas Terhadap Komitmen Organisasi Pada PT.Allianz Life: Analisis Korelasi - Iskandar, Khalid; Ventarini, Rita (Jurnal Ekonomi Kuantitatif Terapan, 2015)
This study aimed to obtain information on the relationship between the independent variables, namely; Leadership (X1) and Task Demands (X2) on the dependent variable is the Organizational Commitment (Y) on PT. Allianz Life, either individually or jointly. The hypothesis tested in this study were: (i) Suspected Leadership positively related to Organizational Commitment; (ii) Anticipated task demands are positively related to Organizational Commitment; (iii) It is assumed jointly Leadership and task demands have a positive relationship to Organizational Commitment. Based on the calculations and Spearman rank correlation analysis results can be seen that the relationship between leadership and task demands on organizational commitment is huge, that is the value of rs by 81% and the rest influenced by other factors. The coefficient of determination stating the contribution of leadership and task demands on organizational commitment by 67% and the remaining contribution of other factors. From the results of hypothesis testing found that t count> t table, namely 6.22> 1.71 so the hypothesis which states that "Leadership and Task Demands Related to Organizational Commitment" unacceptable.
Keywords: leadership; task demands; organizational commitment